1990
DOI: 10.1056/nejm199007053230105
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Endothelium-Dependent Vascular Relaxation in Patients with Essential Hypertension

Abstract: Endothelium-mediated vasodilation is impaired in patients with essential hypertension. This defect may play an important part in the functional abnormalities of resistance vessels that are observed in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
1,071
14
63

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,233 publications
(1,176 citation statements)
references
References 32 publications
28
1,071
14
63
Order By: Relevance
“…12 Moreover, these findings in BS/GS patients are the opposite of those found in hypertensive patients, who have reduced EPCs number, 3,38 increased oxidative stress 42 and altered FMD. 39 Furthermore, the increased number of EPC in BS/GS patients further strengthens the role of Ang II type 1 receptor signaling in EPC biology as BS/GS patients have blunted Ang II type 1 receptor signaling. [21][22][23][24][25][26][27][28] This linkage is further highlighted by the recent report of the beneficial effects of Ang II type 1 receptor blockers on EPCs number and function in hypertensive patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…12 Moreover, these findings in BS/GS patients are the opposite of those found in hypertensive patients, who have reduced EPCs number, 3,38 increased oxidative stress 42 and altered FMD. 39 Furthermore, the increased number of EPC in BS/GS patients further strengthens the role of Ang II type 1 receptor signaling in EPC biology as BS/GS patients have blunted Ang II type 1 receptor signaling. [21][22][23][24][25][26][27][28] This linkage is further highlighted by the recent report of the beneficial effects of Ang II type 1 receptor blockers on EPCs number and function in hypertensive patients.…”
Section: Discussionmentioning
confidence: 81%
“…The correlations noted are likely the result of previously reported relationships between endothelial function and EPC numbers, and function 35,36 along with the relationship between endothelial number and FMD. 37 All of these are altered in hypertension, 3,38,39 and in these alterations oxidative stress has a pivotal role. 40 Relationships between EPCs, FMD and HO-1 LA Calò et al in BS/GS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aging, smoking, obesity, hypertension, dyslipidemia, and diabetes mellitus are well‐known risk factors of endothelial dysfunction 1, 2, 3, 4, 7, 8, 9, 23, 24, 25. We previously showed that ezFMD was significantly correlated with cardiovascular risk factors and endothelial function assessed by FMD in relatively young participants 15.…”
Section: Discussionmentioning
confidence: 99%
“…It is clinically important to assess endothelial function for early detection of atherosclerosis. Several methods have been developed to evaluate endothelial function in humans 3, 4, 5, 6, 7, 8, 9. Measurement of flow‐mediated vasodilation (FMD) in the brachial artery is a noninvasive and broadly applicable method for assessing endothelial function 4, 5, 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the key role that the vascular endothelium plays in atherogenesis, it is not surprising that major cardiovascular risk factors such as hypercholesterolaemia, 8 type 2 diabetes, 21 hypertension, 22 ageing, male gender and smoking, 23 are all accompanied by vascular endothelial dysfunction.…”
Section: Vascular Endothelial Functionmentioning
confidence: 99%